2019
DOI: 10.20902/ijctr.2019.120227
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume Addition in Grace Score as Predictor of Major Cardiovascular Events during Treatment among Acute Coronary Syndrome Patients

Abstract: Background: Acute Coronary Syndrome (ACS) is a term used to describe symptoms caused by Acute Myocardial Infarction (AMI). At present, risk stratification is carried out with the use of a Global Registry of Acute Coronary Events (GRACE) score as a validated predictor for cardiovascular events among ACS patients. Mean platelet volume (MPV) is an accurate marker of platelet size and can be considered that to be added to the GRACE score to increase the predictive value of the occurrence of major cardiovascular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Supporting this notion, two recent studies documented that MPV measurements, in addition to the Global Registry of Acute Coronary Events (GRACE) score, improved the prediction of cardiovascular events among patients with ACS. 48,95 MPV, IPC, and IPF were associated with an increased risk at the relative scale, but this may also translate into a considerably increased risk at the absolute scale. Supporting this, one study found that 18% of patients with MPV >8.9 fL died or had a cardiovascular event within 6 months post-MI.…”
Section: Perspectivesmentioning
confidence: 97%
“…Supporting this notion, two recent studies documented that MPV measurements, in addition to the Global Registry of Acute Coronary Events (GRACE) score, improved the prediction of cardiovascular events among patients with ACS. 48,95 MPV, IPC, and IPF were associated with an increased risk at the relative scale, but this may also translate into a considerably increased risk at the absolute scale. Supporting this, one study found that 18% of patients with MPV >8.9 fL died or had a cardiovascular event within 6 months post-MI.…”
Section: Perspectivesmentioning
confidence: 97%